(untitled) (World Economics and Finance Bulletin, 2024)
The research included the concept of money supply and the factors affecting it, as well as inflation and the factors affecting inflation, that is, the research dealt with the descriptive aspect and the standard aspect based on statistical tools in analyzing the relationship between the money supply as the independent variable, and inflation as the dependent variable), which made the years ( 2004-2023) as limits to the study of measuring the impact of increasing the money supply on raising inflation rates in the Iraqi economy, as the following statistical tools were used in this study, the cointegration model, through the Johansen model, and the results were the presence of a relationship between the two variables, in the short term and the absence of a relationship In the long term, by testing the Johansen model